Pengaruh Metode SAS terhadap Keterampilan Membaca Siswa SD - Siti Robi’ah Al Adawiyah; Diyan Marlina; Fida Rahmantika Hadi (Universitas PGRI Madiun, 2022)
This review plans to decide the effect utilization of the SAS technique to the perusing abilities of 1st grade primary school understudies. This study utilizes quantitative examination strategies with trial techniques. The examination configuration utilized Quasi Experimental Design with Non-identical Control Group Design. The populace in this review were all 1st grade understudies in the District Taman with a sum of 872 understudies. The exploration was directed at SDN 01 Taman Kota Madiun, including class I-A with a sum of 28 understudies and class I-B with a sum of 28 understudies. The inspecting method was completed by likelihood testing with basic irregular examining. The examination instrument was as a perusing expertise execution test. The consequences of the examination utilizing the t-test showed Tcount = 3.082 and Ttable = 2.052 where Tcount > Ttable (3.083 > 2.052) so H0 was dismissed and H1 was acknowledged. So it tends to be inferred that the SAS technique is influence on understudies' understanding abilities.